Normal Liver Stiffness Values in Adult Subjects by Magnetic Resonance Elastography (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Chronic liver disease resulting in fibrosis, and ultimately cirrhosis, is a significant cause of morbidity and mortality worldwide. Conventional imaging techniques such as fibroscan and sono-elastography cannot detect early fibrosis or assess its grade to the histopathologic scale. Liver biopsy, despite being gold standard for detection of liver fibrosis, has limitations and is not well accepted by patients for its invasive nature and potential complications. Magnetic Resonance Elastography (MRE) is a well-established non-invasive newer imaging modality for determining liver stiffness and in most of the cases it can be an alternative to liver biopsy. A comprehensive knowledge of normal liver stiffness is necessary for the early detection of liver fibrosis. Objective: To determine normal liver stiffness values in adult subjects. Materials and methods: The cross-sectional study was carried out in the Department of Radiology and Imaging, BIRDEM General Hospital, Dhaka from October 2021 to September 2023. A total of 60 adult subjects were included in this study according to inclusion and exclusion criteria. Liver stiffness of the selected subjects was measured by MR elastography with a 1.5T MRI scanner through color mapping. The association of liver stiffness with age, sex and BMI of the subjects has also been described.Results: Majority of the subjects belonged to the age-group 30-39 years and were predominantly female. Mean stiffness of the subjects was 2.42±0.20 kPa, with a range of 1.72-2.92 kPa. Mean stiffness for males and females were 2.46±0.19 kPa and 2.40±0.21 kPa respectively. Gender, age, and BMI did not exhibit any significant correlation with mean liver stiffness (p>0.05). Conclusion: The study determined normal liver stiffness values in adult subjects and stiffness did not have a statistically significant correlation with age, sex or BMI.